Interleukin-37 in respiratory diseases: molecular mechanisms and immune modulation - Cao, Jing; He, Kun; Chen, Zixiao; Xu, Haibo; Wei, Jiaona; Yan, Xixin; Song, Beibei (Frontiers in Immunology, 2025)
Interleukin-37 (IL-37) is a potent anti-inflammatory cytokine that plays a crucial protective role in cancer, autoimmune diseases, and inflammatory diseases though its unique dual intracellular and extracellular action pathways. This review highlights the significance of IL-37 in common respiratory diseases. Specifically, IL-37 can alleviate asthma by inhibiting Th2/Th17 immune responses, inhibiting the release of epithelial-derived alarmins (TSLP and IL-33), and attenuating airway remodeling. In pulmonary infections, IL-37 modulates host responses by mitigating virus-induced hyperinflammation and inhibiting viral replication, as observed in COVID-19 and influenza, while also regulating immunopathology in Mycobacterium tuberculosis and fungal infections. Moreover, in non-small cell lung cancer (NSCLC), IL-37 directly suppresses tumor proliferation and migration, and restrains tumor progression through immunomodulation and angiogenesis regulation. In pulmonary fibrosis, IL-37 reduces collagen deposition and promotes autophagy, thereby counteracting interstitial fibrosis. Collectively, these findings demonstrate that IL-37 serves as a crucial immunomodulator in respiratory diseases, and targeting IL-37 offers novel insights and strategic opportunities for clinical intervention. This review systematically summarizes the molecular mechanisms of IL-37 and discusses its clinical therapeutic potential.